2021
DOI: 10.3390/pharmaceutics13040436
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Skin Barrier Function after Repeated Exposition to Phospholipid-Based Surfactants and Sodium Dodecyl Sulfate In Vivo and Corneocyte Surface Analysis by Atomic Force Microscopy

Abstract: (1) Background: The aim of the study was to evaluate the effect of pure lecithins in comparison to a conventional surfactant on skin in vivo. (2) Methods: Physiological skin parameters were evaluated at the beginning and the end of the study (day 1 and day 4) (n = 8, healthy forearm skin) with an Aquaflux®, skin-pH-Meter, Corneometer® and an Epsilon® sensor. Confocal Raman spectroscopy was employed to monitor natural moisturizing factor, urea and water content of the participants’ skin. Tape strips of treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 64 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…Like any other conventional surfactants, they are amphiphatic molecules that constitute a diverse group of compounds characterised by a structure made up of phospholipids (e.g., lecithin, phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol), proteins or protein hydrolysates [ 36 ] and saponins [ 36 , 65 ]. Recently, it was reported that lecithin can be useful as a skin-friendly surfactant for application in skin care products [ 66 ]. Its impact on skin barrier function was found to be considerably lower than that of strong, conventional anionic surfactants such as harsh sodium lauryl sulfate/sodium dodecyl sulfate.…”
Section: Soaps Vs Syndets: Similarities and Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Like any other conventional surfactants, they are amphiphatic molecules that constitute a diverse group of compounds characterised by a structure made up of phospholipids (e.g., lecithin, phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol), proteins or protein hydrolysates [ 36 ] and saponins [ 36 , 65 ]. Recently, it was reported that lecithin can be useful as a skin-friendly surfactant for application in skin care products [ 66 ]. Its impact on skin barrier function was found to be considerably lower than that of strong, conventional anionic surfactants such as harsh sodium lauryl sulfate/sodium dodecyl sulfate.…”
Section: Soaps Vs Syndets: Similarities and Differencesmentioning
confidence: 99%
“…Its impact on skin barrier function was found to be considerably lower than that of strong, conventional anionic surfactants such as harsh sodium lauryl sulfate/sodium dodecyl sulfate. Thus, its use on sensitive skin with pre-existing conditions such as eczema can be considered and should be explored further [ 66 ].…”
Section: Soaps Vs Syndets: Similarities and Differencesmentioning
confidence: 99%
“…The large difference between the relative dielectric constant of water (εr = 81 C 2 /Nm 2 ) and other substances of the skin (εr < 7C 2 /Nm 2 ) is the basis of the measurement. Changes in the dielectric properties, depending on the surface water content, are registered when the first layer of the skin comes into the scattered field of the condenser, and are converted in arbitrary Corneometer ® units (higher values correspond to better hydrated skin) [19,[32][33][34].…”
Section: Skin Hydrationmentioning
confidence: 99%
“…For cosmetic and dermatological research purposes or in medical practice, the mechanical properties (elasticity and firmness) and other parameters of the skin layers (such as hydration, transepithelial water loss, sebum, and melanin level) can be quantitatively evaluated by the specific probes of the Cutometer MultiProbe Adapter (MPA) 580 modular system. The effectiveness of a new product on wrinkles' profile, depth, and the surface can be examined through the fringe projection and 3D images of the skin topography acquired, without any contact, by an innovative device (DermaTop) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Workers at the factory are in direct contact with the materials used in the tofu manufacture without protective equipment so that they have the risk of dermatitis (Badriah & Heriana, 2020). Damage skin components, such as moisturizing factor (NMF) and intercellular lipids consequences of irritants increase the TEWL and cause the skin to become dehydrated and if left unchecked (Vater et al, 2021), it will cause disease complaint, such as DKI. According to the explanation above (Makmur, 2022), added with the absence of data on the hydration levels of hand skin in tofu factory workers in Matraman District, East Jakarta, the researchers are interested in conducting research on the skin overview hydration levels in the hand skin of tofu factory workers in its area (Simpson, 2019).…”
Section: Introductionmentioning
confidence: 99%